Improvement in The Function of Isolated Rat Pancreatic Islets through Reduction of Oxidative Stress Using Traditional Iranian Medicine - Mahban Rahimifard; Mona Navaei-Nigjeh; Neda Mahroui; Sanaz Mirzaei; Zahra Siahpoosh; Amir Nili-Ahmadabadi; Azadeh Mohammadirad; Maryam Baeeri; Reza Hajiaghaie; Mohammad Abdollahi (Cell Journal, 2014)
Objective: Pancreatic islets have fewer antioxidant enzymes than other tissues and thus are vulnerable to oxidative stress. In the present study, the effects of nine specifically selected Iranian medical plants on the mitochondria function and survival of isolated rat islets were examined. Materials and Methods: In this experimental study, following laparotomy, pancreases of rats were removed and the islets isolated and incubated in vitro for 24 hours. Logarithmic doses of plant materials were added to the islets and incubated for an additional 24 hours after which the viability of the cells and production of reactive oxygen species (ROS) were measured. Levels of insulin production in relation to static and stimulated glucose concentrations were also determined. Results: The tested compounds markedly increased survival of the islet cells, their mitochondrial activity, and insulin levels at the same time as reducing production of ROS. Greatest effects were observed in the following order: Peganum harmala, Glycyrrhiza glabra, Satureja hortensis, Rosmarinus officinalis, Teucrium scordium, Aloe vera, Zingiber officinale, Silybum marianum, and Hypericum perforatum at doses of 10, 103, 104, 10, 102, 102, 10-1, 10 and 103 μgmL-1, respectively. Conclusion: Based on these results, we suggest that pretreatment with these selected Iranian medical plants can improve the outcomes of pancreas transplants and grafts through the control of oxidative stress damage.